Promotions and Consumer Attitudes towards Traditional Medicine Usage in Central Uganda - Sarah, Nabachwa; Nixon; Nsambu Kijjambu Fredrick, Kamukama (British Journal of Marketing Studies, 2019)
In times of modernity and with advancements in modern medicine, usage for traditional medicine (TM) was expected to have reduced. Instead, TM usage has increased and literature points to a number of predictors; among which is the promotions from the Traditional Health Practitioners (THPs). However, little is known of how the art of communication used by THPs in these promotions, is interpreted by the TM users, which in effect could influence their attitudes hence usage of TM. The objective of the study therefore was to examine the influence of the promotional strategies on the consumer attitudes of TM users in Central Uganda. A sample of 369 respondents was drawn using purposive and snowballing sampling techniques and data was analysed using both SPSS/20 and AMOS/23. Results show that promotions highly correlates with consumer attitude (r=.820, p?.01) and that for every one unit change in promotions, there will be a 27.392 change in consumer attitude. The findings should enable THPs adjust their promotional strategies to be able to take advantage of the most perceived credible promotional strategies, which are highlighted in the study, in order to tap the increasing TM demand. The study was cross-sectional, so there is need for a longitudinal approach should be explored to examine the promotional influence on attitudes across time.